Empowering Education: Exploring Teachers’ Classroom Practices in Vocational Schools - Teuku Zulfikar; Emawati Emawati; Hidayat Al-Azmi (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
Teaching is indeed a complex provision, which requires teachers being competent in many respects. They should be very knowledgeable in subjects they teach; they should also acquire skills in transferring their subject matters; they need to be skillful in classroom management, and are capable of designing and developing teaching materials. For that reasons, teachers should always engage in professional development to guarantee their best performance. Understanding teachers’ ways of classroom practices is the first step for teachers’ professional development. Therefore, it is timely to conduct a classroom research to explore teachers’ performance, and thus this research explored teachers’ classroom practices in six vocational schools in Aceh. The data was collected mainly through observation of the instructional process in the classroom and in the workshop. The research found several effective attributes of teachers, such as creative, interactive, democratic, intelligent, smart, and well-prepared teachers. The study also identified ‘negative’ teachers’ attributes, such as authoritative, dominated, and withdrawn teachers.